Fructone Synthesis from Ethanol and Acetic Acid (Universitas Negeri Semarang, 2022)
Fructone (Ethyl 2-methyl-1,3-dioxolan-2-acetate) is a perfume ingredient with an apple scent. This study aims to synthesize fructone through the steps of synthesizing ethyl acetate from ethanol and acetic acid, synthesizing ethyl acetoacetate from ethyl acetate through the Claisen condensation reaction, and synthesizing fructone through the acetylation reaction of ethyl acetoacetate with ethylene glycol. Determination of the optimum conditions for the reaction is done by varying the temperature, reagents, catalysts, and time. The reaction products were analyzed by GC and GCMS. It was found that the conversion of ethyl acetate with H2SO4 catalyst and p-toluene sulfonic acid (PTSA) at 75 oC was almost the same, namely 96.63% for H2SO4 catalyst and 96.02% for PTSA catalyst. The optimum conditions for the synthesis of ethyl acetoacetate at a temperature of 82 oC, mole ratio of ethyl acetate, ethanol, and sodium 2:1:1, reaction time for 2 hours with ethyl acetoacetate conversion of 91,55%. The fructone formation reaction using the cyclohexane-water azeotrope technique gave more product than without using the azeotrope technique. The optimum condition for the synthesis of fructone compounds at a temperature of 78 oC, the ratio of moles of ethyl acetoacetate, ethylene glycol and H2SO4 catalyst is 1:2:0.06, the reaction time is 2 hours with the resulting fructone conversion of 87.07%.